The Relationship Between Workload and Fatigue Level with Nurse Performance in Inpatient Ward - Tri Nurdianto; Muhammad Abdurrouf; Dyah Wiji Puspita Sari (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Nurse performance play role important in ensure quality service health and safety patients at home sick. Demands high jobs in the ward care stay often cause burden hard work and fatigue related work, which can impact negative on performance nurse. Condition this need investigated for ensure service maintenance optimal nursing care. Research this aim for know level burden work, level fatigue related work and performance nurses, and analyze connection between burden work and fatigue related work with performance nurse in the ward care stay House Sari Asih Hospital Karawaci, Tangerang City. Research this use design observational analytic with cross-sectional approach. Population consists of from all over nurses working in the ward care stay House Sari Asih Hospital Karawaci, using technique taking total sample. Data collected use questionnaire burden work , fatigue and performance. Data analysis was Chi-Square test. Research results show that 50.6% of nurses own burden work low and 49.4% have burden work high. Nurses who experience fatigue related work amounted to 52.9%, while 47.1% did not experience fatigue. Nurse performance categorized good in 51.8% of respondents and bad in 48.2%. The Chi-Square test shows significant relationship between burden work and performance nurses (p = 0.003) and between fatigue related work and performance nurses (p = 0.021). Workload and fatigue related work relate with performance nurse in the inpatient ward of “Sari Asih” Hospital Karawaci City. Managing burden work and prevent fatigue related work required for increase performance nurse. Keywords : burden work; fatigue related work; performance nurse